DEVELOPMENT OF STUDENTS 'CREATIVE ABILITIES THROUGH THE IMITATION-GAME APPROACH TO TRAINING ORGANIZATIONS (Pedagogy of Higher and Secondary Education, 2001)
The ways of development creative faculty of the students are examined in this article. The examples of the business-like l>lays that were suspended in the articles, are used in process of the training psycho-pedagogic discipline.